The role of school principals in implementing the free nutritious meal program: a case study from indonesian elementary education - Meri Andani; Rambat Nur Sasongko; Azizatul Khairi (Education and Social Sciences Review, 2026)
School nutrition programs are increasingly recognized as strategies for improving children’s health and learning readiness. In Indonesia, the Free Nutritious Meal Program (MBG) was introduced to address nutritional deficiencies among elementary school students. However, research on school leadership in managing such programs remains limited. This study examines the role of school principals in implementing the MBG program and its perceived contribution to student health and learning readiness. A qualitative descriptive case study was conducted at State Elementary School No. 22 Central Bengkulu, Indonesia. Data were collected through semi-structured interviews, non-participant observations, and document analysis involving the principal, six teachers, one Nutrition Program Implementation Unit (SPPG) officer, and several students. Thematic analysis using the Miles and Huberman interactive model revealed four major themes. First, collaborative leadership practices were reflected in the principal’s coordination of implementation teams, distribution schedules, stakeholder communication, and engagement with teachers, parents, and SPPG officers. Second, supervisory practices included monitoring food quality, student discipline, cleanliness, and implementation procedures to ensure program quality. Third, several implementation challenges were identified, including limited storage facilities, food distribution delays, repetitive menus, communication barriers, and limited monitoring systems. Fourth, according to teacher and student reports, the MBG program positively influenced attendance, concentration, discipline, motivation, perceived health, and learning readiness. This study contributes to the limited literature on school leadership in nutrition program implementation and highlights the importance of collaborative leadership, adequate infrastructure, and continuous monitoring in sustaining program effectiveness.